Moral Sensitivity and Work Values as Determinants of Work Engagement among Barangay Health Workers (International Journal of Scientific Research and Management (IJSRM), 2024)
This paper explores Moral Sensitivity and Work Values as determinants of Work Engagement. The respondents of the study were 300 barangay health workers from the Local Government Units of Monkayo, Maragusan, Montevista, Compostela, and New Bataan in Davao de Oro Province, chosen using proportionate stratified sampling. Three adapted questionnaires from web sources were utilized in collecting the data. The items in each indicator revealed good interpretation for both validity and reliability measures. This study utilized a descriptive-correlational method of research design that measures associations of variables. Weighted mean, Pearson r, and regression analysis were utilized in analyzing the data. The study aligns with the United Nations Sustainable Development Goals 3, 8, and 16. The results revealed that the respondents have high levels of moral sensitivity, work values, and work engagement. The relationship between moral sensitivity and work engagement, as well as work values and work engagement, was found to be statistically significant, with a p-value of <0.001. Furthermore, the results also show that there was a significant influence of moral sensitivity and work values on work engagement. Implications of the study findings are presented.